Transformational Leadership, Job Satisfaction, and Employee Performance in Southeast Asian SMEs - Roy, Kavita; Swargiary, Khritish (International Research Journal of Business Studies, 2025)
This study investigates the influence of transformational leadership on employee performance in small and medium enterprises (SMEs) across Southeast Asia, focusing on Malaysia, Singapore, and Thailand. Employing a quantitative cross-sectional survey design, data were gathered from employees using validated scales such as the Multifactor Leadership Questionnaire, Job Satisfaction Survey, Organizational Culture Assessment Instrument, and Employee Performance Scale. Structural equation modeling analysis revealed that transformational leadership positively impacts both job satisfaction and employee performance, with job satisfaction partially mediating this relationship. Organizational culture, particularly clan and hierarchy type, moderates these effects, with clan culture enhancing the leadership-satisfaction link and hierarchy culture diminishing the leadership-performance link. Cross-country differences indicate a stronger leadership-satisfaction effect in Malaysia. These findings highlight the pivotal role of leadership and culture in driving SME performance in Southeast Asia.